2011
DOI: 10.1186/1556-276x-6-258
|View full text |Cite
|
Sign up to set email alerts
|

Round-robin test on thermal conductivity measurement of ZnO nanofluids and comparison of experimental results with theoretical bounds

Abstract: Ethylene glycol (EG)-based zinc oxide (ZnO) nanofluids containing no surfactant have been manufactured by one-step pulsed wire evaporation (PWE) method. Round-robin tests on thermal conductivity measurements of three samples of EG-based ZnO nanofluids have been conducted by five participating labs, four using accurate measurement apparatuses developed in house and one using a commercial device. The results have been compared with several theoretical bounds on the effective thermal conductivity of heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Enhanced thermal conductivity results of ZnO/ethylene glycol nanofluid (27% for 5 vol%) are reported by Wei Yu 12 . ZnO nanofluids have been studied extensively for their thermal and heat transfer properties through round robin test and the results confirm the discrepancy between experimental and theoretical values 13 . ZnO nanofluids have shown hysteresis during heating and cooling cycles 14 and extensive studies have been performed an their physiochemical properties 15,16 .…”
mentioning
confidence: 54%
“…Enhanced thermal conductivity results of ZnO/ethylene glycol nanofluid (27% for 5 vol%) are reported by Wei Yu 12 . ZnO nanofluids have been studied extensively for their thermal and heat transfer properties through round robin test and the results confirm the discrepancy between experimental and theoretical values 13 . ZnO nanofluids have shown hysteresis during heating and cooling cycles 14 and extensive studies have been performed an their physiochemical properties 15,16 .…”
mentioning
confidence: 54%
“…In some cases, this loss of coordination favored the appearance of superficial planes. This type of plane is observed in nanoparticles and originated by minimizing energy [41].…”
Section: Resultsmentioning
confidence: 97%
“…They observed that k nf enhancement increases monotonously with nanoparticle loading, whereas the temperature effect on nanofluids largely depends on the type of nanoparticle and base fluid pairing. A recent study by Lee et al [26] introduced round-robin tests on thermal conductivity measurements of three samples of EG-based ZnO nanofluids. The experiments were conducted in five laboratories, where four of them used measurement apparatuses developed in house and one used a commercial device.…”
Section: Review Of Experimental Evidencementioning
confidence: 99%